INFORMATION SYSTEMS OF EDUCATIONAL PURPOSE OF THE DEPARTMENT OF INFORMATICS, SOFTWARE ENGINEERING AND ECONOMIC CYBERNETICS OF THE KHERSON STATE UNIVERSITY: HISTORICAL AND METHODOLOGICAL ASPECTS - Lvov (Kherson State University, 2018)
The article is devoted to the history of research of the methodological, technological and methodical problems of the development, implementation and use of informational systems of educational assignment, performed at the Department of Informatics, Software Engineering and Economic Cybernetics of the Kherson State University during the 30 years of its existence. It was opened in 1988 under the name Department of Informatics and Computer Science of the Kherson State Pedagogical Institute. The article presents the description of the historical stages of the department development, highlights the key points that have greatly influenced the direction of scientific and methodological work. The article contains the achievements of the team of the Department of Informatics, Software Engineering and Economic Cybernetics, as well as the Research Institute of Information Technologies, which was opened as a part of the University in 2004. The development, implementation and use of programm educational systems as a result of fruitful scientific and scientific-methodical work of teachers and students are presented. The description of the developed software systems, including mathematical software systems, developed in cooperation with the Institute of Cybernetics of the Academy of Sciences of the USSR at that time is suggested. The list of staff of the Department, defended the dissertation on physical, mathematical or pedagogical sciences was given. It is the main result of many years of research in the field of development, implementation and use of information systems of educational purposes. The article contains the list of literature. There are articles by the scientists of the department, devoted to the problem of the development, implementation and use of information systems for educational purposes.